Technological Capabilities of Countries, Firm Rivalry and Foreign Direct Investment - Anand, Jaideep; Kogut, Bruce (Journal of International Business Studies, 1997)
Studies on foreign direct investment (FDI) have concentrated on sectoral effects, but rarely on country patterns, In this paper, we use U.S. Department of Commerce data to identify the largest country shares of new FDI entries into the U.S. and the technological motivations for their investments. Based on the technological intensities of major investing countries in manufacturing industries, we conclude that technological industries attract a disproportionate share of FDI entries. However, the acquisition of U.S. technology is not a major motivation. The findings indicate that industry rivalry is an important dimension to understanding FDI.